Age-dependent changes in anti-Müllerian hormone levels in Lebanese females: correlation with basal FSH and LH levels and LH/FSH ratio: a cross-sectional study - Racoubian, Eddie (BMC Womens Health, 2020)
BACKGROUND: To investigate the age-dependent changes in circulating anti-Müllerian hormone (AMH) levels in healthy Arabic-speaking Lebanese women, and to correlate changes in serum AMH levels with serum FSH and LH values, and LH/FSH ratio. METHODS: Cross-sectional study, involving 1190 healthy females, age 17–54 years, with regular menses and both ovaries. Serum AMH levels (ng/ml) were measured by ELISA. RESULTS: There was an inverse proportion of AMH and subject’s age, which declined from median 6.71 (2.91) ng/ml in young subjects, to 0.68 (0.45) ng/ml in subjects older than 50 years. Average yearly decrease in median AMH levels was 0.27 ng/ml/year through age 35, but then diminished to 0.12 ng/ml/year afterwards. Receiver operating characteristic curve analysis demonstrated high sensitivity and specificity of age as determinant of AMH levels. In contrast to AMH, FSH levels increased progressively from 5.89 (0.11–62.10) ng/ml in young subjects, to 38.43 (3.99–88.30) ng/ml in subjects older than 50 years. On the other hand, age-dependent changes in LH/FSH ratio paralleled those of AMH. Linear regression modeling testing the independent effect of AMH on FSH and LH, adjusted for age, showed that AMH was significant predictor of FSH and LH/FSH ratio, but not LH. This did not contribute significantly to baseline LH and FSH prediction. CONCLUSIONS: Circulating AMH levels are inversely related to age as also shown elsewhere, and are predictors of LH/FSH ratio and FSH but not LH levels in eumenorrheic females.